Zoneamento geoambiental do município de Itápolis (SP) - Felisbino, Robson [UNESP] (2006)
The chosen area for accomplishment of this work was the Itápolis municipality, located in the west portion of the Sao Paulo State. The choice was due to absence of environmental works in the region, necessary because of intense agricultural activities. In this context, the goal was to carry out a survey of environmental features of the area and after analysis, to elaborate environmental zoning of the municipality, based on Mateo Rodriguez (1994) proposal which makes interpretation through system analysis. Through this methodological proposal, the municipality was divided in diverse units and each one of them, the ecological status is established according to capacity of potential use and present social and economic function. The application of this methodology was satisfactory, supplying relevant environmental vulnerability data making possible an environmental analysis of the municipality whose major problems are the intense erosive processes in course as a result of land use without conservatives practices.